2006
DOI: 10.1038/nature04856
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenic transformation by CPI-17 through inhibition of a merlin phosphatase

Abstract: The tumour suppressor protein merlin (encoded by the neurofibromatosis type 2 gene NF2) is an important regulator of proliferation in many cell and tissue types [1][2][3][4] . Merlin is activated by dephosphorylation at serine 518 (S518), which occurs on serum withdrawal or on cell-cell or cell-matrix contact 5,6 . However, the relevant phosphatase that activates merlin's tumour suppressor function is unknown. Here we identify this enzyme as the myosin phosphatase (MYPT-1-PP1d). The cellular MYPT-1-PP1d-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(154 citation statements)
references
References 31 publications
5
149
0
Order By: Relevance
“…Phosphorylation of Merlin at Ser518 was previously reported to play an important role in regulating Merlin tumor suppressor activity (Shaw et al, 2001;Alfthan et al, 2004;Jin et al, 2006a). Interestingly, the interaction between Merlin and VprBP is independent of Ser518 phosphorylation of Merlin (data not shown), suggesting that the Merlin-VprBP interaction might represent a new means for Merlin regulation in vivo.…”
Section: Identification Of Vprbp and Ddb1 As Merlin-associated Proteinsmentioning
confidence: 83%
See 1 more Smart Citation
“…Phosphorylation of Merlin at Ser518 was previously reported to play an important role in regulating Merlin tumor suppressor activity (Shaw et al, 2001;Alfthan et al, 2004;Jin et al, 2006a). Interestingly, the interaction between Merlin and VprBP is independent of Ser518 phosphorylation of Merlin (data not shown), suggesting that the Merlin-VprBP interaction might represent a new means for Merlin regulation in vivo.…”
Section: Identification Of Vprbp and Ddb1 As Merlin-associated Proteinsmentioning
confidence: 83%
“…Phosphorylation of a C-terminal serine (S518) by p21-activated kinase (PAK)-or cAMP-dependent protein kinase A weakens Merlin's self-association and is believed to inactivate its growth-suppressing activity. On the other hand, the phosphatase MYPT-1-PP1-d activates the tumor suppression activity of Merlin through S518 dephosphorylation, which subsequently inhibits the Ras/ERK (extracellular signal-regulated kinase) pathway (Shaw et al, 2001;Alfthan et al, 2004;Jin et al, 2006a). In addition, Merlin can also be regulated at the protein level by growth arrest stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Its expression can suppress cell motility and inhibit the phosphorylation of extracellular signal-regulated kinase and myosin light chain (Twal et al, 2001). Moreover, FBLN1 can reduce the intracellular calcium level, which is important for the activation of multiple signal cascades such as the Ras/MAPK pathway (Twal et al, 2001;Jin et al, 2006Jin et al, , 2007. Interestingly, FBLN1 plays an important role in human papillomavirus (HPV) E6-mediated oncogenesis (Du et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, it has been argued that Merlin mediates both contact inhibition and tumour suppression by directly modulating mitogenic signal transduction at or near the plasma membrane [21,22]. Analysis of various cell types indicated that Merlin can potentially affect a variety of mitogenic pathways, such as Rac-PAK signalling [7,[23][24][25], activation of mTORC1 independently of Akt [26,27], the EGFR-Ras-ERK path- [26,27], the EGFR-Ras-ERK path-,27], the EGFR-Ras-ERK pathway, the PI3K-Akt pathway and FAK-Src signalling [28][29][30][31]. In addition, genetic studies in Drosophila and mice showed that Merlin contributes to the activation of the Hippo tumoursuppressor pathway [18,32,33].…”
Section: Introductionmentioning
confidence: 99%